2008
DOI: 10.1017/s002221510800385x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of melatonin against gentamicin ototoxicity

Abstract: These findings confirm the occurrence of outer hair cell loss after gentamicin treatment, and the attenuation of such loss following simultaneous melatonin injection, using the method of morphological evaluation. These results suggest that melatonin protects against gentamicin ototoxicity by interfering with cytotoxic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 14 publications
3
21
0
2
Order By: Relevance
“…Treatment of rats with MLT protected against GM‐induced ototoxicity as shown by the auditory function results and by the histological assays of HCs present in the cytocochleograms. These findings are in accord with Ye et al . (2009), who observed that MLT attenuated HC loss caused by exposure of guinea pigs to an ototoxic level of gentamicin.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Treatment of rats with MLT protected against GM‐induced ototoxicity as shown by the auditory function results and by the histological assays of HCs present in the cytocochleograms. These findings are in accord with Ye et al . (2009), who observed that MLT attenuated HC loss caused by exposure of guinea pigs to an ototoxic level of gentamicin.…”
Section: Discussionsupporting
confidence: 93%
“…Treatment of rats with MLT protected against GM-induced ototoxicity as shown by the auditory function results and by the histological assays of HCs present in the cytocochleograms. These findings are in accord with Ye et al (2009), who observed that MLT attenuated HC loss caused by exposure of guinea pigs to an ototoxic level of gentamicin. MLT has previously been demonstrated to have both antiinflammatory and neuroprotective properties by reducing IL-1b and TNF-a levels and by inhibiting the phosphorylation of p38, JNK and ERK1/2 in a spinal cord injury model (SCI; Esposito et al, 2009).…”
Section: Mlt Treatmentsupporting
confidence: 91%
“…This latter complex plays a key role in recognizing intracellular electrophils and also natural phenolics and antioxidant vitamins, thus responding to redox perturbations through the expression of genes that are under the control of the nuclear antioxidant responsive element (121). The broad spectrum of metabolic genes regulated by this signaling with a role in cell protection might contribute to explaining how melatonin prevents the cytotoxic effects of drugs such as gentamicin that was used as a factor to induce ototoxicity in guinea pigs (158) and xenobiotics with neurotoxic and prooxidant activity (159) and testicular toxicity (160).…”
Section: Melatonin Metabolism and Cell Protectionmentioning
confidence: 99%
“…Melatonin was put forward as a potent free radical scavenger and an antiapoptotic agent in utricular hair cells . The studies observed that melatonin attenuated hairy cell loss caused by exposure to an ototoxic level of gentamicin …”
Section: Discussionmentioning
confidence: 99%
“…34 The studies observed that melatonin attenuated hairy cell loss caused by exposure to an ototoxic level of gentamicin. 35,36…”
Section: Discussionmentioning
confidence: 99%